The continuing saga of the proposed Malaysian Press Council: a boone or bane? - Shuaib, Farid Sufian; Haron, Hafidz Hakimi (2016)
The newspapers are regarded as the fourth estate in the system of government relating to their function to observe, comment or even investigate government’s activities on behalf of the public. The press has the power to mould public opinion with its reach in readership and influence. The powers also come together with the potential abuse. With its wide readership and influence, individual and corporate reputation and business may be destroyed with writings of false stories in the press. Thus, there is a need to control such power and one of the means to control it is through the establishment of a press council. One criticism of this proposal is the press in Malaysia is already burdened with onerous laws. This paper examines the development of the proposal by various stakeholders to establish a press council since 1973 and the competing interests for and against this proposal. The paper also looks at the possible fate of this proposal considering the long period it is held in abeyance. The research employs textual analysis. The paper concludes with the possibility of such a press council to be established through statutory means.